2017
DOI: 10.18632/oncotarget.23383
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of autophagy-attenuated calcium oxalate crystal-induced renal tubular epithelial cell injury in vivo and in vitro

Abstract: Accumulating evidence suggests that autophagy is involved in the pathophysiological processes of kidney diseases. However, the role of autophagy in the formation of calcium oxalate (CaOx) nephrolithiasis remains unclear. In this study, we investigated the effects of autophagy on renal tubular epithelial cell injury induced by CaOx crystals in vivo and in vitro. We first observed that the expression levels of LC3-II and BECN1 and number of autophagic vacuoles were markedly increased in the renal tissue of CaOx … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 42 publications
3
34
0
Order By: Relevance
“…Autophagy is also associated with a variety of pathological conditions, such as neurodegeneration, cardiomyopathy’ and cancer [33]. Liu et al clearly demonstrated that autophagy activated via the reactive oxygen species pathway is deleterious in CaOx crystal-induced HK-2 cell injury [22]. The autophagy level that was observed in the current study was directly observed under confocal microscopy but also indirectly by the expression of LC3, Beclin-1, and Bcl-2 (Fig.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Autophagy is also associated with a variety of pathological conditions, such as neurodegeneration, cardiomyopathy’ and cancer [33]. Liu et al clearly demonstrated that autophagy activated via the reactive oxygen species pathway is deleterious in CaOx crystal-induced HK-2 cell injury [22]. The autophagy level that was observed in the current study was directly observed under confocal microscopy but also indirectly by the expression of LC3, Beclin-1, and Bcl-2 (Fig.…”
Section: Discussionsupporting
confidence: 56%
“…Liu et al also demonstrated that CaOx crystal retention can induce autophagy in vivo and in vitro and aggravate HK-2 cell injury. Chloroquine diphosphate inhibits autophagy, and renal injury and the formation of nephrolithiasis markedly decreases [22]. …”
Section: Discussionmentioning
confidence: 99%
“…However, treatment with autophagy inhibitor chloroquine significantly decreased the levels of the above indicators in stone model. In addition, we have previously demonstrated that autophagy was deleterious in CaOx crystal-induced renal tubular epithelial cell injury [20]. Therefore, we inferred that autophagy activation may be further promoted the formation of CaOx kidney stones.…”
Section: Discussionmentioning
confidence: 77%
“…CaOx‐induced kidney stone formation is a very complex process involved with oxidative stress, inflammation, autophagy, and exocrine body, and so on . Recently, the interaction between the crystal and renal tubular epithelial HK‐2 cells has been considered as an important factor in the process of stone formation, such as the adhesion and endocytosis of crystals to cells.…”
Section: Discussionmentioning
confidence: 99%